2021
DOI: 10.1038/s41598-020-79398-5
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation-induced changes in the PDZ domain of Dishevelled 3

Abstract: The PDZ domain of Dishevelled 3 protein belongs to a highly abundant protein recognition motif which typically binds short C-terminal peptides. The affinity of the PDZ towards the peptides could be fine-tuned by a variety of post-translation modifications including phosphorylation. However, how phosphorylations affect the PDZ structure and its interactions with ligands remains elusive. Combining molecular dynamics simulations, NMR titration, and biological experiments, we explored the role of previously report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…To further test our hypothesis, we employed a Dsh2-S267E mutant. A previous study demonstrated that Dsh3 also has an interaction between the C-terminal PBM (PDZ-binding motif) and its own PDZ domain 54 . This interaction can be regulated by post-translational modifications including phosphorylation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further test our hypothesis, we employed a Dsh2-S267E mutant. A previous study demonstrated that Dsh3 also has an interaction between the C-terminal PBM (PDZ-binding motif) and its own PDZ domain 54 . This interaction can be regulated by post-translational modifications including phosphorylation.…”
Section: Resultsmentioning
confidence: 99%
“…This interaction can be regulated by post-translational modifications including phosphorylation. Interestingly, the point mutation (Serine 263 to Glutamic acid) suppressed the intramolecular interaction of the PDZ domain and the C-terminal motif resulting in the open conformation of Dsh3 54 . Since Dsh2 and 3 have a highly conserved PDZ domain and PBM, we made the same single amino acid mutation (S267E) in Dsh2 to test whether the open conformation of Dsh2 is more efficient at interacting with WERDS components.…”
Section: Resultsmentioning
confidence: 99%
“…Also, supramolecular intracellular condensates of DVL2 colocalize with centrosomal proteins such as γ-globulin and CEP164 in a Wnt-dependent and cell cycle-dependent manner (Schubert et al, 2022). Lastly, post-translational modification of DVL residues through acetylation or phosphorylation can also regulate DVL nuclear accumulation (Sharma et al, 2019), as well as DVL protein-protein interactions through PDZ domain activity (Jurasek et al, 2021). A previous study linked DVL3 phosphorylation patterns to its function (Hanáková et al, 2019).…”
Section: Discussionmentioning
confidence: 99%